The Relationship of Knowledge With Elderly’s Motivation Following Posyandu For The Elderly in Jorong Jorong Baruah Gunuang - Rahmita Rahman; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
The background of this research is the lack of motivation of the elderly to participate in the  posyandu for the elderly in Jorong Baruah Gunuang 1. The lack of knowledge of the elderly is thought to be due to the lack of knowledge about the existence of the posyandu for the elderly in Jorong Baruah Gunuang1. This study aims to: 1) describe the knowledge of the elderly about the posyandu for the elderly  2) describe the motivation of the elderly to follow the posyandu for the elderly; 3) looking at the relationship between knowledge and motivation in the elderly to follow the posyandu for the elderly in Jorong Baruah Gunuang 1. This type of this research is correlational quantitative research. The population in this study was taken by the elderly in Jorong Baruah Gunuang 1, totaling 58 people, aged 60-70 years, who did not attend the elderly posyandu. The sample was taken as much as 52% with a total of 30 peoples, the technique of this research is  using random sampling. The data collection techniques used were questionnaires and tests, while the data collection tools were a list of statements and questions. The technique used to analyze the data in this study are the percentage formula and product moment. The results showed that: (1) The knowledge of the elderly in  posyandu for the elderly is categorized as low, (2) the motivation of the elderly to follow the posyandu for the elderly is categorized as low, (3) there is a significant relationship between knowledge and motivation of the elderly to participate in posyandu for the elderly activities in Jorong Baruah Gunuang 1. The  Suggestion of this study is the person in charge of the program and cadres should do more outreach to the community on the importance of posyandu for the elderly.Keywords: Knowledge, motivation, elderly